Predicting lung metastasis in high-grade osteosarcoma: The role of computed tomography angiography (CTA) signs with a focus on vascular wrapping and the intratumoral vascular network - Zhendong Luo; Tao Ai; Zhiqiang Liu; Litong He; Yanzhen Hou; Yulin Li; Ziyan Zhou; Xinping Shen (Journal of Bone Oncology)
Objective: Osteosarcoma is a highly malignant bone tumor with a high incidence of lung metastases (LM), significantly impacting the 5-year survival rate of patients. This study aims to predict lung metastasis in osteosarcoma based on computed tomography angiography (CTA) signs. Methods: A retrospective study was conducted involving 89 consecutive patients with osteosarcoma. Clinical features and CTA signs, including age, gender, laterality, primary site, type of bone destruction, T stage, periosteal reaction, tumor length, bone marrow involved length, vascular wrapping, and intratumoral vascular network, were evaluated. Univariate and multivariate logistic regression analyses were used to identify risk factors for LM, followed by receiver operating characteristic (ROC) curve analysis. Results: The vascular wrapping and intratumoral vascular network signs were more frequently observed in LM in patients with osteosarcoma (P < 0.05). The intratumoral vascular network remained an independent risk factor in multivariable regression analysis. ROC curve analysis demonstrated that the area under the curve (AUC) of the logistic regression model was 0.804, indicating good predictive accuracy. Conclusion: Preliminary findings suggest that CTA signs, particularly vascular wrapping and the intratumoral vascular network, may have potential utility in predicting lung metastasis (LM) in osteosarcoma patients. The intratumoral vascular network, in particular, was identified as an independent risk factor.